Adapting Under Pressure: Exploring Dynamic Capabilities in the Post-COVID MICE Sector in Hungary - Horvath, Vanda; Galambos, Judit Zsuzsanna (Marketing & Menedzsment, 2026)
AIMS OF THE PAPER This research examines the digital transformation of the Hungarian MICE sector’s response to the COVID-19 pandemic and its subsequent digital transformation. The primary aim is to contribute to the evolving discourse on how the pandemic accelerated digitalisation in MICE tourism industries and to examine how actors in the Hungarian MICE industry recognised changing customer needs during the COVID-19 pandemic related to digital solutions as well as how successfully they adopted and integrated these solutions. METHODOLOGY We investigate the Hungarian – and particularly the Budapest – MICE sector’s digitalisation using the “Dynamic Capabilities Framework” (DCF) to gain insights into how Hungarian event and venue service providers are responding to the challenges posed by the pandemic and to understand their perceptions of the sector’s digitalisation trends. The research methodology employed is a qualitative, semi-structured thematic analysis of expert interviews. MOST IMPORTANT RESULTS The study revealed that the MICE sector in Hungary performed well in recognising and meeting changing customer needs during the pandemic, which is a capability labelled as sensing, but was less capable in gaining market positions, expanding service portfolio, i.e., the MICE sector underperformed in the area of seizing, as well as in terms of creating a long-term organisational transformation. Barriers to development have been identified including a lack of infrastructural background, financial resources and burdens in management mindset and decision-making. The expected outcome is an overview of the market situation of the players, an analysis of development trends and perceptions of competitiveness, aiming to provide a comprehensive picture for decision-makers. RECOMMENDATIONS The results of the research on the Dynamic Capabilities of the MICE sector may contribute to supporting policymakers in building policy and strategy, such as event and destination management companies or tourism agencies. Results on consumer attitude can enhance the local and regional competitiveness of venue providers, conference centres, exhibition venues, and technical background companies.